Kebijakan Pengelolaan Program Bantuan Operasional Sekolah (BOS) dalam Peningkatan Kualitas Pendidikan Madrasah di Kabupaten Kerinci - Hamdi (JURNAL ILMIAH GEMA PERENCANA, 2023)
This policy paper reviews the School Operational Assistance Fund, or BOS for short, namely government funding for schools. The BOS funds are a form of the Indonesian government's attention to quality education, but in their management, there are still irregularities. Therefore, this article discusses BOS fund management policies to improve madrasa education and to minimize all forms of fraud and ineffectiveness in its management in Kerinci Regency. So, a strategy is needed to effectively manage BOS funds to improve the quality of madrasa education in Kerinci Regency. This article uses a qualitative writing method with a descriptive analysis approach to obtain relevant data according to the problem that is the object of study, accompanied by secondary data analysis and direct interviews conducted in-depth (in-depth interviews) with seven (seven) heads of Madrasah Ibtidaiyah, Madrasah Tsanawiyah, and Madrasah Aliyah, both public and private. The results of this study show that there is ineffectiveness in the management of BOS funds in Kerinci Regency due to non-compliance with procedures, weak comprehensive monitoring and evaluation, and inadequate public complaint tools for the misappropriation of funds. The Kerinci Regency Ministry of Religious Affairs Office has not yet prepared a public complaint tool for the misappropriation of BOS funds. To ensure that BOS funds are on target, socialization, evaluation, and monitoring are needed both internally and externally by the school. Transparent, accountable, and professional policies are very necessary.